Cross-platform assessment of genomic imbalance confirms the clinical relevance of genomic complexity and reveals loci with potential pathogenic roles in diffuse large B-cell lymphoma. Issue 4 (2nd April 2016) - Dias, Lizalynn M.; Thodima, Venkata; Friedman, Julia; Ma, Charles; Guttapalli, Asha; Mendiratta, Geetu; Siddiqi, Imran N.; Syrbu, Sergei; Chaganti, R. S. K.; Houldsworth, Jane
Abstract: Genomic copy number alterations (CNAs) in diffuse large B-cell lymphoma (DLBCL) have roles in disease pathogenesis, but overall clinical relevance remains unclear. Herein, an unbiased algorithm was uniformly applied across three genome profiling datasets comprising 392 newly-diagnosed DLBCL specimens that defined 32 overlapping CNAs, involving 36 minimal common regions (MCRs). Scoring criteria were established for 50 aberrations within the MCRs while considering peak gains/losses. Application of these criteria to independent datasets revealed novel candidate genes with coordinated expression, such as C NOT2, potentially with pathogenic roles. No one single aberration significantly associated with patient outcome across datasets, but genomic complexity, defined by imbalance in more than one MCR, significantly portended adverse outcome in two of three independent datasets. Thus, the standardized scoring of CNAs currently developed can be uniformly applied across platforms, affording robust validation of genomic imbalance and complexity in DLBCL and overall clinical utility as biomarkers of patient outcome.